Extreme Heat Vulnerability of Subsidized Housing Residents in California. Issue 5 (2nd September 2020) - Gabbe, C. J.; Pierce, Gregory
ABSTRACT: Extreme heat is the leading weather-related cause of mortality in the United States, but there is little evidence about how this climate hazard affects residents of different housing types. In this study, we examine whether Californians living in subsidized housing are more vulnerable to extreme heat than those living in unsubsidized housing. We create a tract-level data set combining housing characteristics, downscaled climate projections, and an index of adaptive capacity and sensitivity to heat. We analyze exposure and vulnerability to heat by housing type and location. We find that subsidized housing is disproportionately located in the hottest tracts that simultaneously also have the most sensitive populations and barriers to adaptation (high-high tracts). Whereas 8% of California's housing units are in high-high tracts, these tracts contain 16% of public housing units, 14% of Low-Income Housing Tax Credit units, and 10% of Section 8 Housing Choice Vouchers. Our findings indicate the need for targeted housing and land-use policy interventions to reduce heat vulnerability.